2000
DOI: 10.1515/jpem.2000.13.s1.695
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Age Incidence of Precocious Puberty in Girls: A Multicentric Study

Abstract: We review the etiology and age incidence of precocious puberty in 438 girls examined between 1988-1998; 428 (97.7%) had central precocious puberty (CPP), the remaining 10 (2.3%) gonadotropin-independent precocious puberty (GIPP) of ovarian origin. The majority of CPP girls (59.6%) were aged between 7-7.9 yr, 22.4% were 6 year olds, and only 18% were under 6 years old. Cranial CT and/or MRI performed in 304/428 girls, showed neurogenic abnormalities in 56/304 (18.4%) CPP girls; 30 (9.9%) were due to previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 15 publications
8
95
0
6
Order By: Relevance
“…Previous studies on biochemical evaluation of girls with precocious puberty and its variants are relatively small (8) or based on multicenter studies using different hormone assays (9). Our results, carried out in a larger cohort, confirmed Lee et al's (6) findings of high specificity of a single basal LH sample and its usefulness for establishing the diagnosis of CPP.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies on biochemical evaluation of girls with precocious puberty and its variants are relatively small (8) or based on multicenter studies using different hormone assays (9). Our results, carried out in a larger cohort, confirmed Lee et al's (6) findings of high specificity of a single basal LH sample and its usefulness for establishing the diagnosis of CPP.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the age at the time of diagnosis (7.12±1.18 years) and the age at the time of onset of the complaints (6.46±1.17 years) were found to be close to the literature data in idiopathic CPP cases. Cicternino et al (20) reorted that 59.6% of the CPP patients were diagnosed between the ages of 7 and 8 years, whereas organic CPP patients were diagnosed earlier (<4 years) (20). When Giabicani et al (18) classified idiopathic CPP cases by age groups, it was found that the age at the time of diagnosis was <3 year in 2.2%, 2-6 years in …”
Section: Discussionmentioning
confidence: 99%
“…In girls, CPP is frequently idiopathic and the mean age at the time of diagnosis is higher in cases of idiopathic CPP compared to the cases with organic cause (20). In a large-scale study in which girls with a diagnosis of CPP were evaluated (493 female patients), the mean age at the time of onset of the complaints was found to be 6.68±1.35 years and the age at the time of diagnosis was found to be 7.55±1.44 years (18).…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a su etiología demostrable, la PPC puede resultar del compromiso directo o indirecto de la región hipotalámica por lesiones tumorales intracraneales o alteraciones hormonales, como es el caso de las pubertades precoces periféricas que pueden activar la secreción pulsátil de GnRH (hiperplasia suprarrenal congénita, síndrome de Mc Cune Albright, hipotiroidismo primario descompensado, entre otros) (54) . El diagnóstico clínico, por lo general, se realiza en base a la aparición y progresión de los caracteres sexuales secundarios y la aceleración de la velocidad de crecimiento; y se confirma con la aceleración de la maduración ósea, el desarrollo de los órganos reproductivos y la activación de la secreción pulsátil de la GnRH que reactiva el eje HHG (55,56) ; por lo que la PPC también recibe la denominación de pubertad precoz dependiente de GnRH.…”
Section: Pubertad Precoz Central (Ppc) En Niñasunclassified